The countervailing effects of competition on public goods provision: When bargaining inefficiencies lead to bad outcomes - Gottlieb, Jessica; Kosec, Katrina (Cambridge University Press, 2019)
Political competition is widely recognized as a mediator of public goods provision through its salutary effect on incumbents’ electoral incentives. We argue that political competition additionally mediates public goods provision by reducing the efficiency of legislative bargaining. These countervailing forces may produce a net negative effect in places with weak parties and low transparency—typical of many young democracies. We provide evidence of a robust negative relationship between political competition and local public goods using panel data from Mali. Tests of mechanisms corroborate our interpretation of this relationship as evidence of legislative bargaining inefficiencies. To explore the generalizability of these findings, we analyze cross-country panel data and show that political competition leads to better (worse) public goods provision under high (low) levels of party system institutionalization. The paper sheds light on why political competition is only selectively beneficial, and underscores the importance of considering both the electoral and legislative arenas.